Experiences and Challenges of Midwives in Providing Emergency Maternal Care in Rural Areas East Kalimantan: A Qualitative Study - Dian Ekta Sari; Faridah Hariyani (Universitas Satya Terra Bhinneka, 2026)
Maternal mortality in Indonesia remains high, with rural and remote regions disproportionately affected due to systemic barriers in emergency care. Objectives: This study explores the experiences and challenges of midwives providing emergency maternal care in East Kalimantan, focusing on systemic barriers, clinical autonomy, and professional dedication. Methods: A qualitative exploratory design was employed, involving semi‑structured one‑on‑one interviews conducted online via Zoom with eight midwives working in geographically isolated areas. Data were analyzed using Braun and Clarke’s thematic analysis, supported by NVivo coding. Results: Three overarching themes emerged: (1) systemic barriers and geographical isolation that delay referrals and emergency responses, (2) autonomous clinical decision‑making under resource constraints, and (3) the ethos of dedication and expanded professional roles beyond standard midwifery practice. Midwives reported reliance on poor transport routes, minimal equipment, and lack of supervision, often making rapid clinical decisions without institutional support. Despite these constraints, they demonstrated resilience and commitment, frequently assuming roles beyond maternal care, including general health services and community leadership. Conclusion: Midwives in rural East Kalimantan play a critical role in bridging systemic gaps in emergency maternal care. Their experiences highlight the urgent need for policy reforms to strengthen referral systems, improve emergency transport, expand continuing professional development, and ensure equitable distribution of doctors and specialists. Addressing these challenges is essential to reduce maternal mortality and achieve health equity in Indonesia’s rural communities.